(untitled) (Journal of Parents and Teachers, 2026)
Many children will begin primary education under the new LOGSE reform, which extends compulsory education to age 16. This article presents the educational changes that accompany this new reform. It describes the new model of learning to learn through creative and critical processes. It also addresses the greater autonomy that educational centres will have in organising their activities.